Soil carbon dynamics of oil palm plantations of different ages - Law, Mei Ching (2019)
Soil Carbon (C) studies in oil palm cultivation have generated much interest due to its large-scale planting and its large biomass production that could contribute to soil C sequestration. This three-part research explored the spatial and vertical distributions of Soil Organic Carbon (SOC), and its labile fraction in oil palm cultivation. In part-1, the spatial variability of SOC across five palm age groups, i.e. 1, 5, 10, 17 and 27 Year After Planting (YAP), was characterized. A total of 60 georeferenced topsoil samples (0-20 cm) were obtained for each operational zone: Weeded Circle (WC), Frond Heap (FH) and Avenue (AVE) in a cluster of four palms. Spatial characterization was done using classical and geo-spatial statistics. Results showed that all operational zones of the five palm age groups exhibited a definable spatial structure with moderate to strong spatial dependence, described by either spherical or exponential models. Operational zones of 5 and 27 YAP exhibited a shorter and a longer effective range, respectively, than the other palm age groups, indicating the distance between sampling locations with heterogeneous characteristics are closer for young oil palm plantations than mature oil palm plantations. Part-2 aimed at quantifying SOC dynamics of oil palm cultivation across palm ages, operational zones and soil depths (0-20, 20-40 and 40-60 cm), including a replanting area and secondary forest, each with four sampling clusters. Results showed that SOC contents and stocks of the study sites decreased down the soil profiles. The SOC contents and stocks of FH were the highest, followed by WC and AVE at 0-20 cm depth. Considering the percentage area of each operational zone, AVE possessed the highest SOC stock, followed by FH and WC. This indicates that percentage area of operational zones would affect the SOC stock of the oil palm plantation. The SOC stocks of all study sites were not statistically different at 0-20 and 20-40 cm, except for 17 YAP, which showed the lowest SOC stock. This was attributed to lower clay content and higher sand content, suggesting the essential role of soil texture in the accumulation of SOC stocks in oil palm plantations. Part-3 quantified the Labile C (CL) using 333 mM potassium permanganate (KMnO4) oxidation method, and established the Carbon Management Index (CMI) for oil palm cultivation. Both CL and SOC content shown similar trends at different soil depths and operational zones. At 0-20 cm, the CL contents and CMI values of 1, 5, 10 YAP and replanting were significantly lower than those of secondary forest, 17 and 27 YAP. Conversely, the CMI values increased from 1 to 27 YAP, indicating the increment of palm age and supply of organic materials could improve the CMI values. The CMI values of 10 and 5 YAP were statistically different from secondary forest at 20- 40 and 40-60 cm, respectively. Overall, this research demonstrated an increase in SOC stocks with greater length of time under oil palm cultivation, and that spatial variability assessment will provide more precise quantification of SOC stocks by considering the operational zones in oil palm cultivation.